Advancements in net-zero pertinency of lignocellulosic biomass for climate neutral energy production. (June 2022) - Nahak, B.K.; Preetam, S.; Sharma, Deepa; Shukla, S.K.; Syväjärvi, Mikael; Toncu, Dana-Cristina; Tiwari, Ashutosh
Abstract: The lignocellulosic biomass is one of the most abundantly perennial available natural resources for green energy production. The heterogenous organic and inorganic composite structure of lignocellulosic biomass comprises numerous morphologies, particle size and properties. The cellulose, hemicellulose, lignin, and other organic components with acetyl groups, minerals, and phenolic compounds are found in the biomass as principal ingredients. This review article describes the use of lignocellulosic biomass as sustainable source of energy in solid, liquid and gas with its readiness level in climate neutral energy production. The efficacy of various used physical, chemical, and biological treatments on biomass are discussed with their effect on biomass during conversion of energy sources. Further, the properties of derived energy generations to solid, liquid and gas are described in comparison to commercially used fuels to create a measurable standardization towards their sustainable functions. Data from India's case-study is analyzed in the light of new programs encouraging net-zero utility of lignocellulose biomass. Graphical abstract: The applications of lignocellulose biomass for transportation, heat generation and electricity. Image 1 Highlights: State-of-the-art variables for lignocellulosic biomass. Overview the production of bioenergy from lignocellulosic biomass. Investigated economic feasibility of pre-treatment. Utilization of lignocellulosic waste for the generation of net-zero energy. Figuring out the climate neutral biomass.